2016
DOI: 10.3892/mmr.2016.4959
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of BMSCs with TZD solution decreases the proliferation rate of MCF-7 cells by reducing FGF4 protein expression

Abstract: The present study aimed to investigate the effects of bone marrow-derived mesenchymal stem cells (BMSCs) that had been pretreated with pioglitazone and/or rosiglitazone on the growth and proliferation rate of MCF-7 cells. The adhesive interaction between the BMSCs and the MCF-7 cancer cells revealed that the pretreatment of BMSCs with a combination of two types of thiazolidinedione drug reduced the growth and proliferation rate of the MCF-7 cells. The proliferation rate of the MCF-7 cells could also be reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Considering that pioglitazone has been reported to possess anticancer effects (200)(201)(202), it may be beneficial to examine the possibility of priming MSCs with pioglitazone for cancer therapy. After all, using MSCs pretreated with pioglitazone as a strategy to improve the overall therapeutic effects, as reported in our study (199), remains rare. Despite the study on cardiomyogenic transdifferentiation and cardiac function (203), as mentioned above, MSCs pretreated with pioglitazone for cancer therapy remain to be characterized.…”
Section: Potential Strategy In Utilizing Mscs For Cancer Therapymentioning
confidence: 82%
See 1 more Smart Citation
“…Considering that pioglitazone has been reported to possess anticancer effects (200)(201)(202), it may be beneficial to examine the possibility of priming MSCs with pioglitazone for cancer therapy. After all, using MSCs pretreated with pioglitazone as a strategy to improve the overall therapeutic effects, as reported in our study (199), remains rare. Despite the study on cardiomyogenic transdifferentiation and cardiac function (203), as mentioned above, MSCs pretreated with pioglitazone for cancer therapy remain to be characterized.…”
Section: Potential Strategy In Utilizing Mscs For Cancer Therapymentioning
confidence: 82%
“…Other studies using pioglitazone as the priming agent also found similar results, where pretreated MSCs had greater therapeutic effects on lung regeneration in an emphysema mouse model ( 197 , 198 ). Pioglitazone has been administered indirectly to breast cancer cells via stem-and-cancer cell interaction ( 199 ). Through this process, modified and viable pretreated stem cells are subsequently administered to patients, and pretreated stem cells are allowed to interact with cancer cells in the patients' bodies.…”
Section: Potential Strategy In Utilizing Mscs For Cancer Therapymentioning
confidence: 99%
“…Fibroblast growth factor 4 [FGF4] is a member of the FGF superfamily, which is involved in numerous stages of embryonic development and enhances multiple oncogenic activities, including tumor proliferation, invasion/migration, and colony initiation abilities [63,64]. Although there are some reports on the involvement of FGF4 in the processes of cancers, including lung adenocarcinoma, colorectal cancer, breast cancer, and ovarian cancer [65][66][67][68], little is known about the involvement of FGF4 in HCC. In this study, we found, for the first time, that FGF4 was highly expressed in HCC, suggesting a role as a novel serum biomarker for HCC.…”
Section: Discussionmentioning
confidence: 99%